Optimizing maturity‐onset diabetes of the young detection in a pediatric diabetes population. Issue 4 (10th March 2022) - Menon, Sruthi; Refaey, Ahmad; Guffey, Danielle; Balasubramanyam, Ashok; Redondo, Maria J.; Tosur, Mustafa
Abstract: Introduction: Maturity‐onset diabetes of the young (MODY) is often misdiagnosed as type 1/type 2 diabetes. We aimed to define patient characteristics to guide the decision to test for MODY in youth with diabetes. Research Design and Methods: Of 4750 patients enrolled in the Diabetes Registry at Texas Children's Hospital between July 2016 and July 2019, we selected ("Study Cohort", n = 350) those with: (1) diabetes diagnosis <25 years, (2) family history of diabetes in three consecutive generations, and (3) absent islet autoantibodies except for GAD65. We retrospectively studied their clinical and biochemical characteristics and available MODY testing results. Cluster analysis was then performed to identify the cluster with highest rate of MODY diagnosis. Results: Patients in the Study Cohort were 3.5 times more likely to have been diagnosed with MODY than in the overall Diabetes Registry (4.6% vs. 1.3%, p < 0.001). The cluster ( n = 16) with the highest rate of clinician‐diagnosed MODY (25%, n = 4/16) had the lowest age (10.9 ± 2.5 year), BMI‐z score (0.5 ± 0.9), C‐peptide level (1.5 ± 1.2 ng/ml) and acanthosis nigricans frequency (12.5%) at diabetes diagnosis (all p < 0.05). In this cluster, three out of five patients who underwent MODY genetic testing had a pathogenic variant. Conclusions: Using a stepwise approach, we identified that younger age, lower BMI, lower C‐peptide, and absence of acanthosis nigricans increase likelihood of MODY in racially/ethnically diverse children with diabetes who have a multigenerational family history of diabetes and negative islet autoantibodies, and can be used by clinicians to select patients for MODY testing.